A Survey on the Metaverse: The State-of-the-Art, Technologies, Applications, and Challenges - Wang, Hang; Ning, Huansheng; Lin, Yujia; Wang, Wenxi; Dhelim, Sahraoui; Farha, Fadi; Ding, Jianguo; Daneshmand, Mahmoud (IEEE internet of things journal, 2023)
In recent years, the concept of the Metaverse has attracted considerable attention. This article provides a comprehensive overview of the Metaverse. First, the development status of the Metaverse is presented. We summarize the policies of various countries, companies, and organizations relevant to the Metaverse, as well as statistics on the number of Metaverse-related publications. Characteristics of the Metaverse are identified: 1) multitechnology convergence; 2) sociality; and 3) hyper-spatio-temporality. For the multitechnology convergence of the Metaverse, we divide the technological framework of the Metaverse into five dimensions. For the sociality of the Metaverse, we focus on the Metaverse as a virtual social world. Regarding the characteristic of hyper-spatio-temporality, we introduce the Metaverse as an open, immersive, and interactive 3-D virtual world which can break through the constraints of time and space in the real world. The challenges of the Metaverse are also discussed.